Baricitinib Improvement Across Regions in Atopic Dermatitis Patients with Baseline Body Surface Area up to 40% and Severe Itch - José-Manuel Carrascosa; Alessandra Narcisi; Toshifumi Nomura; Sonja Ständer; Christian Vestergaard; Silvia Sabatino; Susanne Grond; Uffe Koppelhus; Mohamed Elrayes; Yun-Fei Chen; Chunyuan Liu; Andreas Wollenberg (Adis, Springer Healthcare, 2024)
Abstract Introduction Patients with moderate-to-severe atopic dermatitis (AD) who are most likely to respond to the Janus kinase (JAK) 1/2 inhibitor baricitinib (BARI) are known to have an impacted body surface area (BSA) ≤ 40% and severe itch (numerical rating scale [NRS] ≥ 7], collectively termed 'BARI itch-dominant' patients. Our objective is to build on our previous work by providing a body region-specific, clinical characterization of the BARI itch-dominant patient at baseline and their response to BARI 4 mg. Methods BREEZE-AD7 was a phase 3 trial in adults with moderate-to-severe AD receiving placebo or 2 mg or 4 mg BARI in combination with topical corticosteroids. Assessing only data from BARI itch-dominant patients, we summarized the baseline characteristics and conducted body region-specific analyses on Eczema Area and Severity Index (EASI) data in order to report the response to placebo versus BARI 4 mg within this patient subtype. Results BARI 4 mg was highly effective across all body regions; at week 16, 75% improvement was seen in EASI scores (EASI75), and response rates with BARI 4 mg (head/neck, 58.3%; trunk, 69.2%; upper extremities, 61.5%; lower extremities, 87.5%) all exceeded those with placebo (head/neck: 37.5%; trunk, 40.6%; upper extremities, 18.8%; lower extremities, 40.6%) as well as the overall EASI75 rates of the intent-to-treat (ITT) population (BARI, 48.0%; placebo, 23.0%). At baseline, most BARI itch-dominant patients presented with involvement of all regions (mean regional BSA 22.7%-40.3%), highest in the head and neck, mean EASI region scores of 15.7-24.0, and considerably severe sign ratings (mean EASI sub-scores: 1.4-2.3, out of 3), especially for erythema. Conclusion BARI itch-dominant patients exhibit AD involvement across all body regions and considerable sign severity, especially erythema. In response to BARI 4 mg, EASI quickly improved across regions, substantially more so in this subtype than in the ITT population.